Common dementia screening procedures: DSM-5 fulfilment and mapping to cognitive domains. (4th April 2022) - Thabtah, Fadi; Spencer, Robinson; Peebles, David
Dementia is diagnosed by a specialised clinician based on the patient's cognitive abilities in different areas. Since there is an ever-growing variety of cognitive medical procedures available, it can be hard to assess where each procedure fits in the process of screening AD, and more notably, how the contents of these procedures, i.e. tests and activities, map to cognitive domains assessed during the screening process. Therefore, this research reviews and critically analyses a selection of the common dementia cognitive screening procedures such as the Alzheimer's Disease Assessment Scale - Cognitive Subscale (ADAS-Cog), Clinical Dementia Rating Scale Sum of Boxes (CDR-SB), Everyday Cognition (ECog), and others. More importantly, we map screening procedures components including cognitive tests, questions and activities to the cognitive domains outlined in the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM-5). We found that no screening procedure covers the complete cognitive domains specified by DSM-5.